Pengembangan LKPD Berbasis Masalah Open Ended Untuk Menumbuhkan Berpikir Kreatif Peserta Didik Kelas X Dan Menunjang Pembelajaran Daring - Arrasyid, Maulana Fatiehurrizqie; Karim, Karim; Sari, Asdini (Mandalika Mathematics and Educations Journal, 2021)
This study aims to produce teaching materials in the form of open-ended problem-based student worksheets on trigonometry material to support online learning and foster creative thinking skills in class X students and find out the responses of teachers and students to the developed student worksheets. This study used a 4-D model, but only three out of four stage are done which are define, design, and develop. Data collection techniques were carried out using validation sheets and questionnaires for teacher and student. Validation was carried out by three experts and the response questionnaire was tested in response to five teachers and five students. The data obtained will be analyzed qualitatively and quantitatively. The score obtained from the validation sheet is 88.14% with very valid criteria. While the score obtained from the teacher response questionnaire is the number of teachers whose scores are in the practical category more than the number of teachers whose scores are in the impractical category and the score obtained from the student response questionnaire is the number of students whose scores are in the readable category more than the total number of students whose scores fall into the illegible category. This means that student worksheets meets the criteria of practicality and legibility.